"Enlightened System" or "Regulatory Nightmare"?: New York's Adirondack Mountains and the Conflicted Politics of Environmental Land-Use Reform During the 1970s. (13th June 2019) - Siskind, Peter
Abstract: This exploration of the politics of land-use reform in New York's vast Adirondack Mountains provides a revealing window onto the ambiguities, evolution, and importance of environmental liberalism during the 1970s. A distinctive set of circumstances, featuring forceful advocacy by Governor Nelson Rockefeller and propitious political timing, led to the creation in the early 1970s of one of the most ambitious state-level environmental reforms in modern American history. But implementation during the mid- and late 1970s proved challenging. Environmental management by a new regional agency that possessed powerful regulatory authority over all public and private lands in the region produced discontents, distrust, and organized opposition among both developers and property-rights advocates on the right and environmental advocates on the left. The result was an uneasy, enduring legacy: the new regulatory institution and key environmental planning ideas of the early 1970s and the later, wide-ranging discontents would coexist in similar forms for decades to come.